2005
DOI: 10.1136/gut.2004.055251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ondansetron, a 5-HT3 receptor antagonist, on fatigue in chronic hepatitis C: a randomised, double blind, placebo controlled study

Abstract: Background and aims: There are no available effective therapies for fatigue associated with chronic hepatitis C (CHC). The serotonin antagonist ondansetron has been shown to be effective in the chronic fatigue syndrome. In this randomised, placebo controlled, double blind trial, we investigated the effect of orally administered ondansetron on fatigue in CHC. Methods: Thirty six patients with CHC were included if fatigue was their predominant symptom and they scored more than 4 on a visual analogue scale (0-10)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 30 publications
2
47
0
2
Order By: Relevance
“…Use of ondansetron which is a competitive antagonist of serotonin receptors has ameliorated fatigue in HCV infected patient. Also, the placebo controlled randomized study of thirty six HCV infected patients have shown an improved fatigue and depression scores with ondansetron [61] . These studies have shown an important role of serotoninergic pathway dysfunction that causes fatigue, reduced level of serum tryptophan, and a reduced synthesis of serotonin [62,63] .…”
Section: Mechanisms Contributing To Neurological Dysfunctionmentioning
confidence: 99%
“…Use of ondansetron which is a competitive antagonist of serotonin receptors has ameliorated fatigue in HCV infected patient. Also, the placebo controlled randomized study of thirty six HCV infected patients have shown an improved fatigue and depression scores with ondansetron [61] . These studies have shown an important role of serotoninergic pathway dysfunction that causes fatigue, reduced level of serum tryptophan, and a reduced synthesis of serotonin [62,63] .…”
Section: Mechanisms Contributing To Neurological Dysfunctionmentioning
confidence: 99%
“…Despite this, the reported side-effects between the placebo and ondansetron groups were not different. In addition, other studies on ondansetron efficacy in treating depressive and anxiety symptoms (concomitant to or even derived from other illnesses) have successfully tested doses between 8 and 24 mg daily, reporting a reduction in depressive symptoms [21,34], decrease of anxiety in subjects with Obsessive Compulsive Disorder [35], and even improvement on cognitive impairments among schizophrenics [36]. Also, 8 mg ondansetron (but not 4 mg) was shown to be useful for decreasing opiate withdrawal signs [37].…”
Section: Discussionmentioning
confidence: 99%
“…4,5 It has been used as a treatment for tic disorders, 6 tardive dyskinesia, 7 and alcoholism. 8,9 It has also been successfully trialed in patients with tinnitus, 10 fatigue related to chronic hepatitis, 11 and opiaterelated pruritus, 12 but not benzodiazepine withdrawal. 13 Given that antipsychotic drugs can augment the benefits of SRIs in patients with OCD, might ondansetron carry similar benefits?…”
Section: Introductionmentioning
confidence: 99%